Efficient solar cells based on a new polymer from fluorinated benzothiadiazole and alkylthienyl substituted thieno[2, 3-f]benzofuran. (May 2015) - Cui, Ruili; Zou, Yingping; Xiao, Lu; Hsu, Chain-Shu; Keshtov, Mukhamed L.; Godovsky, Dmitri Yu.; Li, Yongfang
Abstract: A new conjugated D-A copolymer, TBFBT, containing a fluorinated benzothiazole electron-acceptor unit and an electron-donor segment of alkylthienyl substituted thieno[2, 3- f ]benzofuran, was synthesized using a Stille coupling reaction. The resulting copolymer was characterized by elemental analysis, GPC, TGA, UV–Vis absorption spectroscopy and cyclic voltammetry measurements. The copolymer was readily dissolved in common organic solvents, exhibited good film forming properties and displayed a broad absorption from 300 nm to 800 nm with a low optical bandgap of 1.56 eV. Cyclic voltammetry measurement gave HOMO and LUMO energy levels of −5.11 eV and −3.49 eV, respectively. Polymer solar cells based on TBFBT: PC61 BM (1:1.5, w/w ) demonstrated an initial power conversion efficiency (PCE) of 4.1% with a V oc of 0.72 V and a J sc of 11.6 mA cm −2 . PSCs based on TBFBT:PC71 BM (1:1.5, w / w, 3 vol% 1, 8-diiodooctane as additive) were further optimized by using methanol. The optimized result exhibited a high PCE up to 6.1% with a high J sc of 14.4 mA cm −2 and FF of 0.62, under the illumination of AM1.5G, 100 mWcm −2 . These investigations indicate that the new copolymer TBFBT is a promising donor material for PSCs and methanol treatment is a simple and effective way to improve PCE. Graphical abstract: Highlights: A new D-A copolymer, TBFBT, was synthesized and characterized. PSCs based on TBFBT:PC71 BM exhibited a high PCE up to 6.1% by using methanol treatment. Improved photovoltaic properties using methanol treatment are accountable to increased mobility and better film morphology.